Assessing the relative impacts and economic costs of Japanese knotweed management methods - Sophie Hocking (Scientific Reports, 2023)
Sustainable land management encompasses a range of activity that balance land use requirements with wider conservation and ecosystem impact considerations. Perennial invasive alien plants (IAPs), such as Japanese knotweed, cause severe ecological and socio-economic impacts, and methods to control their spread also come at a cost. Synthetic herbicides are generally viewed as less sustainable and more ecologically damaging than alternative approaches. Here we used a comparative Life Cycle Assessment to evaluate the sustainability of herbicide-based management approaches and physical alternatives, using a large-scale Japanese knotweed field study as a model IAP system. Glyphosate-based methods elicited the lowest environmental impacts and economic costs during production. Geomembrane covering and integrated physiochemical methods were the costliest and imposed the greatest impacts. We discuss the costs and benefits of chemical and physical approaches for the sustainable management of invaded land and question how sustainable environmental stewardship is defined for the control of IAPs.